Struktur Pendapatan dan Pola Konsumsi Pangan Rumah Tangga Nelayan - Ida Rosada; N Nurliani; Nur Ayufadhilah (JURNAL GALUNG TROPIKA, 2020)
The household income comes from the income of fishermen's household groups (husband, wife, children, and other family members) and works (fishers and non-fishermen). The amount of household income strongly influences the consumption pattern of anglers households. This study aims to analyze the amount of income, food consumption patterns, and the relationship between income and the model of fishermen household food consumption. The population in this study were all fisherman households in Panyula Village, East Tanete Riattang District, Bone Method District. The research's location was carried out purposively, considering that the area is mostly coastal areas, and the livelihood of the community is fishermen. Determining the sample of 10% using a simple random method (simple random sampling), so the number of samples selected is 50 fisherman households. Data were analyzed using the method of income analysis, expected food patterns (PPH), and Chi-square. The results showed that the income structure of fishermen's household originated from the husband's income of 60.3%, the wife 3.8%, the children 30.4%, and the profit of other family members 5.5%. Sources of income based on the type of work, namely from work as fishermen, amounted to 80.5% and alternative jobs other than fishers by 19.5%. The pattern of fishermen's household food consumption based on the Expected Food Pattern is 90% in the shallow category, and there are no respondents insufficient and proper groups. The relationship between income and household food consumption patterns of fishers is not significant.